PENINGKATAN KINERJA APARATUR PEMERINTAH DALAM UPAYA PELAYANAN PUBLIK KEPADA MASYARAKAT - Didik Kusumahadi (REFORMASI, 2012)
Essentially public service is all forms of government services to community either in the form of goods or services, in which the public's right to acquire, both in order to obtain their rights and obligations as citizens countries. In an attempt to obtain a scientific study is needed a systematic and rational frame of mind as well as based on the theory as its foundation. The use of theory is very important in research activities because in it there are key points that connect two or more variables that can be drawn as a logical conclusion. Service is a way of serving, helping to prepare, administering, and completing tasks, needs of a person or group, meaning that the object being served is a society of individuals, groups, and organizations. If a community which is served increasingly feels satisfied, every official should have the skills, expertise, skills or professional in serving, responding to needs, requirements and typical needs of others.